DIFFICULTIES IN THE MENTAL HEALTH NETWORK AND PSYCHIATRIC READMISSIONS: DISCUSSING POSSIBLE RELATIONSHIPS - Déborah Karollyne Ribeiro Ramos; Jacileide Guimarães; Simone Karine da Costa Mesquita (Universidade Federal do Paraná, 2014)
The aim of this study was to identify difficulties existing in the mental health services of Rio Grande do Norte, Brazil and to discuss possible relationships between these and psychiatric readmissions in the state. An exploratory-descriptive, qualitative study was conducted, the corpus of which originated from the transcription of semi-structured interviews, applied with 20 workers of a state reference psychiatric hospital, between June and August 2011. The results were analyzed using thematic content analysis. The categories analyzed in this article are: inadequate operation of outpatient services; difficult access to the substitute services, and the problem of chemical dependency in the context of psychosocial care. It was concluded that the problems highlighted are configured as contemporary challenges for mental health and express the need for a (re)view of the mental health network.